2021
DOI: 10.7554/elife.67624
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPRi screening identifies OCIAD1 as a prohibitin client and regulatory determinant of mitochondrial Complex III assembly in human cells

Abstract: Dysfunction of the mitochondrial electron transport chain (mETC) is a major cause of human mitochondrial diseases. To identify determinants of mETC function, we screened a genome-wide human CRISPRi library under oxidative metabolic conditions with selective inhibition of mitochondrial Complex III and identified ovarian carcinoma immunoreactive antigen (OCIA) domain-containing protein 1 (OCIAD1) as a Complex III assembly factor. We find that OCIAD1 is an inner mitochondrial membrane protein that forms a complex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 108 publications
(160 reference statements)
1
22
0
Order By: Relevance
“…TMEM256 presumably localizes to the inner membrane ( Kustatscher et al., 2019 ), and its complexome profile supports an interaction with the TIM23 core complex ( Figure S6 K). NCBP2-AS2 displays a high molecular mass form similar to PAM16 (TIMM16), DNAJC19 (PAM18/TIMM14), TIMM21, the complex III assembly factor OCIAD1 ( Le Vasseur et al., 2021 ), the mitochondrial disease gene DNAJC30 ( Figure S6 L; Richter-Dennerlein et al., 2014 ; Tebbenkamp et al., 2018 ), the prohibitin protein family ( Figure S6 F), and the high molecular mass form of TIM23 ( Figure S6 M). The TIM23 complex can perform two different functions, distinguished by its association with the presequence translocase-associated motor (PAM) ( Chacinska et al., 2005 , 2010 ; Mick et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…TMEM256 presumably localizes to the inner membrane ( Kustatscher et al., 2019 ), and its complexome profile supports an interaction with the TIM23 core complex ( Figure S6 K). NCBP2-AS2 displays a high molecular mass form similar to PAM16 (TIMM16), DNAJC19 (PAM18/TIMM14), TIMM21, the complex III assembly factor OCIAD1 ( Le Vasseur et al., 2021 ), the mitochondrial disease gene DNAJC30 ( Figure S6 L; Richter-Dennerlein et al., 2014 ; Tebbenkamp et al., 2018 ), the prohibitin protein family ( Figure S6 F), and the high molecular mass form of TIM23 ( Figure S6 M). The TIM23 complex can perform two different functions, distinguished by its association with the presequence translocase-associated motor (PAM) ( Chacinska et al., 2005 , 2010 ; Mick et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using a number of additional bioinformatics tools for predicting TMDs, including TMPred ( Hofmann, 1993 ) and HMMTOP (Bioinformatics Toolkit, RRID:SCR_010277) ( Tusnády and Simon, 2001 ), as well as TMHMM (RRID:SCR_014935) ( Krogh et al, 2001 ) and Phobius (RRID:SCR_015643) ( Käll et al, 2004 ) without the overlap constraint used by UniProt, we identified an additional 30 proteins that had TMDs identified by at least two algorithms. A number of these proteins have been experimentally determined to be genuine membrane proteins, including complex I subunit NDUFB2 through high resolution structural studies ( Zhu et al, 2016 ) recently identified complex III assembly factor OCIAD1 through classical carbonate extraction studies ( Le Vasseur et al, 2021 ) and pro-survival protein FUNDC2 through mutation and localization analysis ( Ma et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…While canonical Notch signaling leads to crystal cell differentiation, non-canonical activation of Notch pathway due to stalling in endosomes of Asrij mutants ( Kulkarni et al, 2011 ) may also contribute to the synergistic effects on phenotype. Asrij/OCIAD1 acts as a transmembrane scaffolding protein that regulates assembly and activation of critical signaling components and molecular complexes across organelles ( Sinha et al, 2013 ; Le Vasseur et al, 2021 ). A recent report shows that OCIAD1 is a client of Prohibitin supramolecular complex that acts as a scaffold for the assembly of mitochondrial electron transport chain Complex III in HEK293T and U2OS cells ( Le Vasseur et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Asrij/OCIAD1 acts as a transmembrane scaffolding protein that regulates assembly and activation of critical signaling components and molecular complexes across organelles ( Sinha et al, 2013 ; Le Vasseur et al, 2021 ). A recent report shows that OCIAD1 is a client of Prohibitin supramolecular complex that acts as a scaffold for the assembly of mitochondrial electron transport chain Complex III in HEK293T and U2OS cells ( Le Vasseur et al, 2021 ). Hence, Asrij may potentially act as mediator of inter-organellar communication that may influence blood cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%